The Safety and Outcomes of Keratopigmentation as a Cosmetic Eye Color Change Procedure - Żak, Sandra; Ruzik, Alicja; Przebieradło, Patrycja; Rędziniak , Patrycja; Rajs, Monika; Gaj-Hunter, Antonina Magdalena; Kowalska, Monika; Żurek, Katarzyna; Stolarska, Kaja; Terpiłowska, Sandra (Journal of Education, Health and Sport, 2026)
We review the articles discussing the rationale for performing keratopigmentation (KTP) for purely aesthetic purposes and the safety considerations associated with this method. Originally developed for therapeutic purposes, such as iris defects and corneal opacities, KTP has recently gained popularity as a permanent cosmetic method for changing eye color. Advances in femtosecond-assisted techniques and the use of micronized mineral pigments have enhanced the precision of the procedure and its biocompatibility, contributing to high patient satisfaction rates. Published data, mainly in the form of case reports and small case series, suggest that cosmetic KTP is generally well tolerated. The most commonly reported adverse effects are mild and reversible. Functional parameters typically remain stable, although reductions in contrast sensitivity and mild endothelial cell loss have been reported. Corrective procedures are often necessary, and repeated interventions may increase the risk of complications. Given the limited long-term evidence and the ethical considerations of performing irreversible surgery on healthy eyes, cosmetic KTP should be approached with caution, ensuring thorough patient counseling and careful candidate selection.